GLOBAL action on school library education and training / edited on behalf of IFLA by Barbara A. Schultz-Jones and Dianne Oberg. Berlin - Faletar Horvatić, Ivana (Vjesnik bibliotekara Hrvatske, 2021)
Global action on school library education and training / edited on behalf of IFLA by Barbara A. Schultz-Jones and Dianne Oberg. Berlin; Boston: De Gruyter Saur, 2019. (IFLA publications; vol. 178). ISBN 978-3-11-061312-4